INKLUSI KEUANGAN DAN TEKNOLOGI, P2P LENDING, KEMISKINAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA AGREGAT - Bawono, Suryaning; Wilantari, Regina Niken (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to find the development of aggregate human resources based on human capital investment in poverty alleviation efforts in Indonesia. The data used is secondary data obtained and processed from the Indonesian Financial Services Authority and the world bank. This study uses a vector error correction model to estimate, simulate, and predict each of the variables studied to provide an overview of the opportunities and threats of technological inclusion and financial inclusion in poverty reduction efforts based on human capital investment in the education-based human capital framework. Inclusion has the potential to be an opportunity to reduce the cost of education so that human capital investment efforts in the framework of education-based human capital work by the poor have a higher chance of success. Financial inclusion support from official P2P lending can also support poor people's capital in investing in human capital, but with low interest and must be close to zero and would be better with zero interest. Keywords: education, financial inclusion, human resources, P2P lending, poverty alleviation